Analisa Pola Pembelian Konsumen Menggunakan Metode Association Rule Pada Data Transaksi Penjualan Dunia Vape - Azhar Radhitya Tarigan; Firahmi Rizky (Universitas Budi Darma, 2025)
Dunia Vape Trading Business is a trading business engaged in the sale of electronic cigarette spare parts. Every consumer who is going to buy a product, the consumer looks at the product shelves one by one to find the product they are looking for. The problem that occurs is that sometimes it is tiring for consumers to search on different shelves or it can also cause consumers not to buy the products they actually need. This is because the products sold are not arranged based on the purchasing patterns that consumers often make. Therefore, a method is needed that can make it easier for consumers to find the desired product and so that UD Dunia Vape can find out consumer purchasing patterns so that it can arrange and provide products according to the usual patterns. Therefore, researchers utilize computer technology to help consumers find the desired product and so that UD Dunia Vape can find out consumer purchasing patterns so that it can arrange and provide products according to the usual patterns. In computer science, one of the methods that can be applied is by using data mining. One of the methods used in determining patterns is the Association Rule Mining Method. Association rule mining is a data mining technique that aims to find association rule patterns between a combination of items. Implementation of the Association Rule Mining Method on sales of goods at the UD Dunia Vape Store is used to provide information on the results of building material sales patterns each month which can be used as parameters in managing UD Dunia Vape's inventory of materials, in addition to providing information on the most popular and most sold building materials at UD Dunia Vape. The results obtained Based on the results and discussion, it can be concluded that the analysis of consumer purchasing patterns using the Association Rule method on Dunia Vape sales transaction data can be applied based on the results of manual method application where the association rule results are the same as data mining application testing, namely if you buy I = LOST VAPE URSA CAP POD KIT JOY PURPLE then Buy N = PODS FRIENDLY ICE PEDIA BLUEBERRY 15MG 30ML (24) with a confidence value of 100% and if you buy N = PODS FRIENDLY ICE PEDIA BLUEBERRY 15MG 30ML (24) then Buy I = LOST VAPE URSA CAP POD KIT JOY PURPLE with a confidence value of 100%.